An exceptional event during the moulting process of an eutardigrade: two bucco-pharyngeal apparatuses present - Pilato, Giovanni; Lisi, Oscar (Zootaxa, 2014)
A specimen of Diphascon (Diphascon) procerum with two bucco-pharyngeal apparatuses (one of which should have been expelled during moulting process) is described, and that anomalous condition is discussed.